Trade Facilitation, Economic Welfare, and Sustainable Development of West and South Africa - Safaeimanesh, Shahrzad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The purpose of this study is to estimate the potential annual economic gain to be had from trade facilitation by the member countries of the South African Customs Union (SACU) and the coastal countries of the Economic Community of West African States (ECOWAS). These measures would decrease the border and documentary compliance time and costs associated with the administration of international trade. They will increase regional trade integration enabling the achievement of the sustainable development goals of these countries. A partial equilibrium welfare economics framework is used. It employs sets of export supply and import demand elasticities for each country that are derived using a general equilibrium estimation method. The annual economic welfare gains resulting from the reduction of excessive trade compliance costs for the ECOWAS region are estimated to between US$1.6 billion to US$2.7 billion (2019 prices). This is between 0.24% and 0.42% of the combined GDPs of these countries. The magnitude of this economic gain is between 6% and 10% of the governments’ budgets assigned for education, and is between 33% and 58% of the amounts of their budgets allocated for health. In the absence of reform, these inefficient practices waste an amount equal to between 15% and 26% of the annual net official development assistance these countries receive. The economic gains for SACU countries from reducing the excess administrative costs for imports and exports of SACU countries would be between US$2.2 billion and US$3.7 billion (2018 prices) or between 0.54% and 0.90% of GDP of the member countries of this region. This gain is 1.6 to 2.6 times greater than the annual net official development assistance received. For South Africa, the gain from reducing these excess compliance costs is between US$2.1 billion and US$3.5 billion, which is 2.3 to 3.8 times greater than the annual development assistance they receive. Keywords: Trade facilitation; West Africa; Economic Community of West African States (ECOWAS); South African Customs Union (SACU); South Africa; Regional Integration; Trade Compliance Costs; Trade Reform; Economic Welfare Gains; Sustainable Development; SDGs 2030.

ÖZ:Bu çalışmanın amacı, Güney Afrika Gümrük Birliği (SACU) üye ülkeleri ve Batı Afrika Devletleri Ekonomik Topluluğu'nun (ECOWAS) kıyı ülkeleri tarafından ticaretin kolaylaştırılmasından elde edilecek potansiyel yıllık ekonomik kazancı tahmin etmektir. Bu önlemler, sınır ve belgesel uyum süresini ve maliyetleri uluslararası ticaretin idaresi ile ilgili azaltacaktır. Bunlar bölgesel ticaret entegrasyonunu artırarak bu ülkelerin sürdürülebilir kalkınma hedeflerine ulaşmasını sağlayacaktır. Kısmi bir denge refah ekonomisi çerçevesi kullanılmaktadır. Genel bir denge tahmin yöntemi kullanılarak türetilen her ülke için ihracat arzı ve ithalat talebi esnekliklerini kullanır. ECOWAS bölgesi için aşırı ticaret uyum maliyetlerinin düşürülmesinden kaynaklanan yıllık ekonomik refah kazançlarının 1,6 milyar ABD Doları ile 2,7 milyar ABD Doları (2019 fiyatları) arasında olduğu tahmin edilmektedir. Bu ülkelerin birleşik GSYİH'larının %0,24 ile %0,42'si arasındadır. Bu ekonomik kazancın büyüklüğü, hükümetlerin eğitim için ayrılan bütçelerinin %6 ile %10'u arasındadır ve sağlık için ayrılan bütçelerinin %33 ile %58'i arasındadır. Reformun yokluğunda, bu verimsiz uygulamalar, yukarıda verilen ülkelerin aldığı yıllık net resmi kalkınma yardımının % 15 ile % 26'sına eşit bir miktarı boşa harcıyor. SACU ülkelerinin ithalat ve ihracatına yönelik fazla idari maliyetleri azaltmanın ekonomik kazanımı 2,2 milyar ABD Doları ile 3,7 milyar ABD Doları (2018 fiyatları) arasında olacaktır. Bu bölgeye üye ülkelerin GSYİH'sinin %0,54 ile %0,90'ı arasındadır. Bu kazanç, alınan yıllık net resmi kalkınma yardımının 1,6 ile 2,6 katıdır. Güney Afrika için, bu fazla uyum maliyetlerinin azaltılmasından elde edilen kazanç, aldıkları yıllık kalkınma yardımından 2,3 ile 3,8 kat daha fazla olan 2,1 milyar ile 3,5 milyar ABD Doları arasındadır. Anahtar Kelimeler: Ticareti kolaylaştırma; Batı Afrika; Batı Afrika Devletleri Ekonomik Topluluğu (ECOWAS); Güney Afrika Gümrük Birliği (SACU); Güney Afrika; Bölgesel entegrasyon; Ticaret Uyum Maliyetleri; Ticaret Reformu; Ekonomik Refah Kazanımları; Sürdürülebilir Kalkınma; SDG'ler 2030.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Economic Conditions and Development-Africa; Trade-International Trade-Africa; Africa-Economic conditions; Africa-Economic policy; Trade facilitation; West Africa; Economic Community of West African States (ECOWAS); South African Customs Union (SACU); South Africa; Regional Integration; Trade Compliance Costs; Trade Reform; Economic Welfare Gains; Sustainable Development; SDGs 2030